SUFI POEM “JOHNNY CASH GOES TO HELL”: THE UNIVERSAL OF MORALS (Universitas Negeri Semarang, 2016)
his research is aimed at finding the theme of a unique Sufi poem expressed by Tiel Aisha Ansari entitled ―Johnny Cash Goes to Hell‖. The analysis used is Riffaterre‘s Semiotic theory. The theory uses two stages of signification. The first finds lexical meaning that is called Heuristic reading. It functions as the footstep for the next signification. The next one explores second meaning that is called Hermeneutic reading. This signification consists of four steps: Hypogram Actual, Hypogram Potential, Model and Matrix. The result of research says that this poem uses character Johnny Cash and St. Peter as the signified. The dialogue was used by Tiel to share Johnny‘s thought. Johnny, the icon for Sufis, was considerate with what people had suffered from. The Hypogram Potential says that a Sufi sacrifices his comfort just for making people who are trapped by wrongness can go back to expedience. The model makes the distribution of meanings to be two, namely morals and universalism. The morals, especially considerate, can be universal. It can go across religions. This can be proved from the using of inter-religion symbols in the poem. That‘s why ―the universal of morals‖ is the theme can be got here.